Mamey sapote fruit and carotenoid formulations derived thereof are dietary sources of vitamin A – A comparative randomized cross-over study - Chacón Ordóñez, Tania (2019)
Mamey sapote is a fruit rich in specific keto-carotenoids, namely sapotexanthin and cryptocapsin. Their chemical structure suggests their provitamin A activity, although their absorption and conversion to vitamin A remained to be demonstrated in humans. Besides structure-related factors, the fruit matrix might also hamper absorption and conversion efficiency. Therefore, we monitored carotenoid and vitamin A levels in triacylglycerol-rich lipoprotein (TRL) fractions in plasma of human participants after consumption of fresh sapote and a carotenoid-rich “matrix-free” formulation derived thereof. A randomized 2-way cross-over study was conducted to compare the post-prandial bioavailability of 0.8 mg sapotexanthin and 1.2–1.5 mg cryptocapsin from the above-mentioned test meals. Seven blood samples were drawn over 9.5 h after test meal consumption. Carotenoids and retinoids were quantitated in TRL fractions using HPLC-DAD. Sapotexanthin was absorbed by all participants from all meals, being ca. 36% more bioavailable from the “matrix-free” formulation (AUCmedian = 73.4 nmol∙h/L) than from the fresh fruit (AUCmedian = 54.0 nmol∙h/L; p ≤ 0.001). Cryptocapsin was only absorbed by 4 of 13 participants. The appearance of retinyl esters was observed in all participants independent of the test meal. Although the fruit matrix hampered carotenoid in vivo-bioavailability from sapote, the fruit clearly represents a valuable source of vitamin A for humans.